Genome of the sea anemone Exaiptasia pallida and transcriptome profiles during tentacle regeneration - Shum, Cheryl W.Y.; Nong, Wenyan; So, Wai Lok; Li, Yiqian; Qu, Zhe; Yip, Ho Yin; Swale, Thomas; Ang, Put O.; Chan, King Ming; Chan, Ting Fung; Chu, Ka Hou; Chui, Apple P.Y.; et al. (Frontiers in Cell and Developmental Biology, 2022)
Cnidarians including sea anemones, corals, hydra, and jellyfishes are a group of animals well known for their regeneration capacity. However, how non-coding RNAs such as microRNAs (also known as miRNAs) contribute to cnidarian tissue regeneration is poorly understood. Here, we sequenced and assembled the genome of the sea anemone Exaiptasia pallida collected in Hong Kong waters. The assembled genome size of E. pallida is 229.21 Mb with a scaffold N50 of 10.58 Mb and BUSCO completeness of 91.1%, representing a significantly improved genome assembly of this species. The organization of ANTP-class homeobox genes in this anthozoan further supported the previous findings in jellyfishes, where most of these genes are mainly located on three scaffolds. Tentacles of E. pallida were excised, and both mRNA and miRNA were sequenced at 9 time points (0 hours, 6 hours, 12 hours, 18 hours, 1 day, 2 days, 3 days, 6 days, and 8 days) from regenerating tentacles. In addition to the Wnt signaling pathway and homeobox genes that are shown to be likely involved in tissue regeneration as in other cnidarians, we have shown that GLWamide neuropeptides, and for the first time sesquiterpenoid pathway genes could potentially be involved in the late phase of cnidarian tissue regeneration. The established sea anemone model will be useful for further investigation of biology and evolution in, and the effect of climate change on this important group of animals.